DEVELOPING INTERACTIVE MEDIA TO TEACH SPEAKING SKILL FOR GRADE 11 STUDENTS - Anggi Yulihar and Nora Ronita Dewi (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2016)
The study deals with the developing interactive media for senior high school students. The objective of this study is to find out how to develop interactive media for better speaking skill of senior high school students. The research was conducted by using Research and Development (R&D). The subject of this research was 2016/2017 students of the eleventh grade of Class XI IPA4 in SMAN 1 Batang Kuis. The number of the students was 30 students. The data of this study was collected by using need analysis questionnaire and experts’ judgment. Need analysis questionnaire was calculated by using percentage to get the information of students’ need before developing interactive media. Experts’ judgment was calculated by using likert data, mean and criteria interval of expert judgment to know the validity of interactive media which has been developed. After the data analyzed, it was found that the experts’ judgment result was 4.80 which had a very good criteria interval. The result of the research find that interactive media is a very good to be used in teaching speaking skill.